PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PERAWAT RAWAT JALAN RUMAH SAKIT ISLAM HARAPAN ANDA TEGAL - Rossyana Fatimah; Ida Wahyuni; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2016)
Job satisfaction is a factor to consider in the maintenance of human resources in the hospital. The lack of job satisfaction can be seen from work absenteeism, indolence in provision of nursing services, as well as the resignation of the job.The purpose of this study is to analyze the influence of leadership and work motivation on job satisfaction of outpatient nurses at RS Islam Harapan Anda Tegal. The type of this research is explanatory research with cross sectional approach and a sample of 26 people. Data analysis using logistic regression to determine the presence or absence of the independent variable influence on the dependent variable. The results of this research note that respondents which rate good leadership have job satisfaction as high as 46.2%. The results of logistic regression test Wald test p value (Sig) amounted to 0.037 <0.05 means there is a significant effect of leadership on job satisfaction. Respondents which rate high motivation have job satisfaction as high as 53.8%. The results of logistic regression test Wald test p value (Sig) amounted to 0,999 ≥0,05 means there is no significant effect of motivation on job satisfaction. It was concluded that there was a significant effect of leadership on job satisfaction while work motivation does not have a significant impact on job satisfaction. It is advisable for companies to facilitate training activities relevant to leadership and motivation of nurses to improve nursing services.